Teacher Vitality and Positive Teacher-Student Relationships: A Study of Emotional Transmission between Teachers and Students - Peng, Kaiping (Best Evidence in Chinese Education, 2024)
The interaction between teachers and students has long been a vital research question among educational researchers. In recent years, incremental attention has been paid to the impact of positive psychological traits and emotions of teachers on teacher-student interactions. Drawing on the vitality theory, this study posited that the vitality of teachers contributed to enhancing students’ vitality and fostering positive teacher-student relationships via the emotional transmission effect, particularly through students’ perception of teacher enthusiasm. This hypothesis was empirically examined with a sample of 2,386 Chinese secondary school students and 76 head teachers.